2013
DOI: 10.1007/s00436-013-3494-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and phylogenetic analysis of Eimeria arloingi in Iranian native kids

Abstract: Among the 16 species of Eimeria from goats, Eimeria arloingi and Eimeria ninakohlyakimovae are regarded as the most pathogenic species in the world and cause clinical caprine coccidiosis. E. arloingi is known to be an important cause of coccidiosis in Iranian kids. Molecular analyses of two portions of nuclear ribosomal DNA (internal transcribed spacer1 (ITS1) and 18S rDNA) were used for the genetic characterization of the E. arloingi. Comparison of the sequencing data of E. arloingi obtained in the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
(31 reference statements)
3
17
0
Order By: Relevance
“…In this study, we obtained similar but not identical outcomes to those obtained by Khodakaram-Tafti et al (2013) that compared the ITS1 sequence of an Iranian E. arloingi isolate with other Eimeria sequences and found it to be most similar to E. bovis, with a more distant relationship to E. zuernii. Comparison of a partial 18S rDNA sequence (637 nt) was also performed, however the phylogeny obtained differed considerably from our own, primarily due to the higher resolution achieved here using a sequence of 2290 nt, while Khodakaram-Tafti et al (2013) used much shorter sequences: 392 nt of ITS1 and 637nt of 18S, studied independently. More recently, a phylogenetic analysis of Eimeria from local infections in Australia have been reported (Al-Habsi et al, 2017) with a slightly different result, mainly explained by the different genes and the length of the sequence analysed.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, we obtained similar but not identical outcomes to those obtained by Khodakaram-Tafti et al (2013) that compared the ITS1 sequence of an Iranian E. arloingi isolate with other Eimeria sequences and found it to be most similar to E. bovis, with a more distant relationship to E. zuernii. Comparison of a partial 18S rDNA sequence (637 nt) was also performed, however the phylogeny obtained differed considerably from our own, primarily due to the higher resolution achieved here using a sequence of 2290 nt, while Khodakaram-Tafti et al (2013) used much shorter sequences: 392 nt of ITS1 and 637nt of 18S, studied independently. More recently, a phylogenetic analysis of Eimeria from local infections in Australia have been reported (Al-Habsi et al, 2017) with a slightly different result, mainly explained by the different genes and the length of the sequence analysed.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, 18S rRNA sequences of E. crandallis and E. ahsata had considerable homology with E. arloingi , E. bovis and E. zuernii (98% - 99%). Similarly, Khodakaram-Tafti et al ( 4 ) reported a close relationship between E. arloingi and bovine ( E. bovis and E. zuernii ) and ovine ( E. ahsata and E. crandallis ) coccidia, based on the 18S sequence analyses. It has also been shown that there is a similarity between these two species ( E. crandallis and E. ahsata ) and E. arloingi , based on microscopic evaluation of their sporulated oocytes.…”
mentioning
confidence: 84%
“…The ITS-1 DNA from each sample was amplified using conventional PCR and the cycling conditions and primer sequences of the forward and reverse primers were as follows: Forward 5′-GCAAAAGTCGTAACACGGTTTCC-3′, Reverse: 5′-CTGCAATTCACAATGCGTATCG-3′ [12] , cycling conditions were: initial denaturation at 94 °C for 5 min followed by 35 cycles of 94 °C for 45 s, 55 °C for 1 min and 72 °C for 1 min, this was followed by a final extension at 72 °C for 7 min. The amplification products from ITS-1 rDNA were separated on 1.6% agarose gel containing 0.4 µg/mL of ethidium bromide at 90 V for 40–60 min, and then imaged.…”
Section: Methodsmentioning
confidence: 99%
“…It depends on the skill and experience of the examiner. Recently, modern molecular techniques have been deployed for Eimeria identification including PCR amplification technique [12] . Nevertheless, the main issue with the PCR procedures is that the Eimeria oocyst wall is extremely robust in addition to the low DNA concentration obtained especially if the oocysts numbers are low in subclinical cases, thus a successful DNA extraction from oocysts is imperative for reliable PCR amplification and detection of Eimeria [13] .…”
Section: Introductionmentioning
confidence: 99%